2017
DOI: 10.1016/j.taap.2017.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral screening of the LOPAC1280 library in zebrafish embryos

Abstract: Spontaneous activity represents an early, primitive form of motor activity within zebrafish embryos, providing a potential readout for identification of neuroactive compounds. However, despite use as an endpoint in chemical screens around the world, the predictive power and limitations of assays relying on spontaneous activity remain unclear. Using an improved high-content screening assay that increased throughput from 384 to 3,072 wells per week, we screened a well-characterized library of 1,280 pharmacologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 43 publications
0
36
1
1
Order By: Relevance
“…They found an effect concentration for the spontaneous tail coiling (STC, conducted in 384-well plates) which is 12-fold higher than that reported in a subsequent study [87] in which embryos were exposed in glass beakers (both used nominal concentrations). Similarly, Vliet et al [118] who also exposed embryos to abamectin in 384-well plates found an effect concentration which is 6 fold higher than that observed in Raftery and Volz [87]. Beside the test container material, the ratio of surface area to volume could also induce variability.…”
Section: Materials Used For Exposure Vesselsmentioning
confidence: 90%
See 3 more Smart Citations
“…They found an effect concentration for the spontaneous tail coiling (STC, conducted in 384-well plates) which is 12-fold higher than that reported in a subsequent study [87] in which embryos were exposed in glass beakers (both used nominal concentrations). Similarly, Vliet et al [118] who also exposed embryos to abamectin in 384-well plates found an effect concentration which is 6 fold higher than that observed in Raftery and Volz [87]. Beside the test container material, the ratio of surface area to volume could also induce variability.…”
Section: Materials Used For Exposure Vesselsmentioning
confidence: 90%
“…This event is assumed to be important for the hatching of the embryo from its chorion but evidence for a role of STC for hatching has not yet been provided [58,98]. Frequency changes of the STC have been used as a tool to detect the effects of neuroactive chemicals in developing embryo [118,121].…”
Section: Types Of Behavioral Tests Considered In This Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Adult 5D zebrafish ( Danio rerio ) were maintained and bred on a recirculating system as previously described by Vliet et al 24 . All embryos were collected immediately after spawning and staged according to previously described methods 25 .…”
Section: Methodsmentioning
confidence: 99%